2011
DOI: 10.1007/s12020-011-9456-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and fatigue in patients with adrenal incidentaloma

Abstract: Results: Reduced QoL was found in patients with adrenal incidentaloma as compared to controls. Dimensions of QoL that were notably affected included mobility (p=0.03), performance of usual activities (p=0.002) and anxiety/depression (p=0.04) as evaluated using the EQ-5D; physical functioning (p<0.001), physical role (p<0.001), general health (p<0.001), vitality (p=0.001), social functioning (p=0.001) and emotional role (p<0.001)as evaluated using the SF-36; and physical fatigue (p=0.04) as assessed using the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Respondents also scored lower on nearly all domains of SF-36, reflecting a generally worse HRQL, compared with age and sex-matched norms from the general population. This is in agreement with the findings of Kastelan et al [22]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Respondents also scored lower on nearly all domains of SF-36, reflecting a generally worse HRQL, compared with age and sex-matched norms from the general population. This is in agreement with the findings of Kastelan et al [22]. …”
Section: Discussionsupporting
confidence: 94%
“…Brunaud et al [21] measured the impact on HRQL of living with an AI using proxy surgeons’ ratings [21]. Kastelan et al [22] recently reported on the HRQL of AI patients seen at a referral centre compared to an age and sex-matched control group.…”
Section: Discussionmentioning
confidence: 99%
“…ACC can be discovered accidentally on imaging done for other purposes or during incidentaloma follow-up. Follow-up for incidentaloma can have an impact on overall HRQoL and anxiety, due to patients’ concerns about possible malignancy of the tumor [32,33]. Similarly, it can be hypothesized that follow-up for recurrence after initial treatment of the tumor can have the same negative impact on HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…Data on HRQoL in patients with tumours in the adrenals are scant [13]. In a case-control study, Kastelan et al demonstrated reduced quality of life in patients with adrenal incidentalomas compared with age- and sex-matched controls [17]. Brunaud et al reported lower QoL, estimated by SF-36, in patients with adrenal tumours before adrenalectomy and at 6-weeks follow-up compared with the French general population [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated reduced HRQoL in patients with adrenal tumours independent of diagnosis [16]. Kastelan et al demonstrated impaired QoL in patients with non-functional adrenal incidentalomas compared with controls [17]. Previous reports that focused on patients with functional tumours reported an improvement in HRQoL after adrenalectomy [18].…”
Section: Introductionmentioning
confidence: 99%